Wali Adhol in Islamic Family Law and Its Relevance to Indonesian Marriage Law - Zamzam Al-Fathoni Fillah; Muhammad Amar Adly; Heri Firmansyah; Mariati Yahya (Jurnal Hukum Keluarga, 2026)
This article examines the concept of wali adhol (reluctant or refusing guardian) within Islamic family law and analyzes its relevance and institutionalization in Indonesian marriage law. A wali adhol refers to a marriage guardian who unjustifiably refuses to solemnize the marriage of a woman under his guardianship despite the fulfillment of Islamic legal requirements. Employing a normative juridical method with conceptual and comparative approaches, this study analyzes classical fiqh doctrines, statutory regulations, and judicial practices in Indonesia. The findings demonstrate that the doctrine of wali adhol has been systematically incorporated into Indonesian positive law through Article 23 of the Compilation of Islamic Law (KHI) and relevant regulations of the Ministry of Religious Affairs. The Religious Courts are vested with the authority to determine the status of wali adhol and to appoint a wali hakim (judicial guardian) as a substitute, thereby safeguarding women’s rights to marriage. This study argues that the regulation of wali adhol reflects a substantive harmonization between Islamic law and national law, grounded in principles of justice, legal certainty, and the protection of human rights.